Evaluation of Traditional Chinese Medicine nursing interventions for patients undergoing chemotherapy for malignant bone tumors (骨肿瘤患者化疗期间的中医护理干预研究) - YANG Qingqing (杨青青); ZHANG Dahua (张大华) (中西医结合护理)
Objective To investigate the effect of Traditional Chinese Medicine (TCM) nursing interventions for patients undergoing chemotherapy for malignant bone tumors. Methods Totally 60 patients with malignant bone tumors were randomly divided into the treatment group and control group, with 30 cases in each group. All patients received routine care during chemotherapy, and those in the treatment group were given TCM interventions. Anxiety and depression status of patients were measured by Self-rating Anxiety Scale (SAS) and Self-rating Depression Scale (SDS). Patient satisfaction was evaluated by a self-made questionnaire. Results The SAS and SDS scores dropped in both two groups after intervention , and were lower in the treatment group than those in the control group (P<0. 05). The rate of patient satisfaction in the treatment group was higher than that in the control group (P<0. 05). Conclusion The TCM nursing is potentially effective to relieve the negative emotions and improve the satisfaction of patients undergoing chemotherapy for malignant bone tumors. (目的 评价在骨肿瘤患者化疗期间应用中医护理干预的效果。方法 骨肿瘤化疗患者60例随机分为治疗组与对照组, 各30例。对照组给予常规护理, 治疗组在对照组基础上增加中医护理干预。分别采用焦虑自评量表(SAS) 和抑郁自评量表(SDS)评估患者焦虑、抑郁情绪, 评价患者满意度。结果 干预后治疗组SAS和SDS评分均较干预前下降, 且治疗组SAS和SDS评分低于对照组, 差异有统计学意义(P<0. 05)。治疗后患者满意率高于对照组(P<0. 05)。结论 骨肿瘤患者化疗期间实施中医护理干预, 能有效缓解焦虑、抑郁情绪, 提升护理满意度。)